Effectiveness of nesting and pronation on oxygen saturation in babies with respiratory distress syndrome - Rahmawati, Eni; Rahmawati, Helda Budi; Purnamasari, Meivita Dewi; Purwandari, Haryatiningsih; Fitriyani, Aris (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Background: The infant mortality rate in Indonesia is still relatively high at 15 per 1000 live births. Cause of Infant death can occur due to intrapartum complications, one of which is a respiratory system disorder in the form of Respiratory Distress Syndrome (RDS). The nesting and prone positions intervention can be made to optimize the oxygenation status of babies with RDS. However, it is necessary to see the effectiveness of both positions in increasing oxygen saturation. Objective: This study aims to determine differences in oxygen saturation in infants with RDS who are given nesting and pronation. Methods: This is a quasi-experimental with a two-group pretest-posttest design. The total sample of 36 respondents was divided into the nesting and pronation group positions with the consecutive sampling technique. Oxygen saturation levels were measured using a pulse oximeter before and after the intervention for 15 minutes in one day. The analytical test is a paired t-test and an independent t-test. Results: The statistical test results for the pretest-posttest difference in oxygen saturation (p<0.05) in the pronation group increased by 3.6% compared to the nesting group by 0.3%, which means that the prone position is better at increasing oxygen saturation. Conclusion: Pronation is more effective in increasing oxygen saturation than nesting in infants with RDS. So, pronation can be used as a nursing intervention in infants with RDS.